An efficient method for the preparation of magnetic Co3O4 nanoparticles and the study of their catalytic application - Ardeshirfard, Hakimeh; Elhamifar, Dawood (Frontiers in Catalysis, 2023)
In this study, magnetic cobalt oxide (Co3O4) nanoparticles (NPs) were synthesized through a new and green method using cobalt chloride hexahydrate (CoCl2.6H2O), pluronic P123 as a stabilizer, and sodium borohydride (NaBH4). The CO3O4 nanoparticles were characterized by diffuse reflectance infrared Fourier transform spectroscopy, powder X-ray diffraction, X-ray photoelectron spectroscopy, energy-dispersive X-ray spectroscopy, scanning electron microscopy, and vibrating sample magnetometer. The magnetic Co3O4 NPs were used as a catalyst with high activity and stability in the synthesis of tetrahydrobenzo[b]pyran derivatives. This reaction was carried out in water, as it is an environmentally friendly solvent, using a low loading of Co3O4 NPs at room temperature. Various derivatives of aldehydes were used as substrates to obtain a high yield of the corresponding tetrahydrobenzo[b]pyrans in short times. In addition, the catalyst was recovered and reused several times with no notable decrease in its activity.